Counting 'micro-workers': societal and methodological challenges around new forms of labour. (1st January 2020) - Tubaro, Paola; Le Ludec, Clément; Casilli, Antonio A.
Abstract : 'Micro-work' consists of fragmented data tasks that myriad providers execute on online platforms. While crucial to the development of data-based technologies, this poorly visible and geographically spread activity is particularly difficult to measure. To fill this gap, we combined qualitative and quantitative methods (online surveys, in-depth interviews, capture-recapture techniques and web traffic analytics) to count micro-workers in a single country, France. On the basis of this analysis, we estimate that approximately 260, 000 people are registered with micro-work platforms. Of these, some 50, 000 are 'regular' workers who do micro-tasks at least monthly and we speculate that using a more restrictive measure of 'very active' workers decreases this figure to 15, 000. This analysis contributes to research on platform labour and the labour in the digital economy that lies behind artificial intelligence.